SLP Research with ICT Modules by ERDCN in Rural Areas of Nepal (Sudurpaschim Spectrum, 2024)
This research paper analyzes the School Library Program (SLP) based on the field of education through skill development, practical, behavioral, and technical knowledge. The research also focuses on the academic performance and behavioral progress, following the issues and rights to education in rural areas of Nepal with the detailed of the designed modules following Quantitative data analysis of pre 21 schools and later on 28 schools’ surveys. In spite of the increase in literacy rates, Nepal has still been facing so many obstacles in achieving quality education, so the role of GOs, NGOs, and INGOs has been proven to be of prime importance to tackle the challenges and obstacles in the field of Nepalese education. With the increasing steps of the 21st century, technical and advanced change, education has turned out to be the primary need of every individual. Consequently, Nepalese educators have become more conscious of dealing with the issues and rights to education.